Integrated Psychomotor LKPD Design Creation Training Physical Literacy to Increase Students Activeness and Critical Thinking in Carrying Out Physical Education Sports and Health Learning Activities - Tatok Sugiarto; Sugiyanto; Arief Darmawan; Ahadi Priyohutomo; Cahyo Nugroho Sigit (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Active involvement of students in physical education is essential for their health, movement activities, and social and cognitive development. However, in the next few years, physical education is predicted to face challenges, especially in encouraging physical activity amidst the rapid advancement of technology that attracts students' attention. Independent Curriculum seeks to provide teachers with the freedom to innovate and adjust learning methods according to student characteristics. One of the relevant tools to achieve this goal is the Student Worksheet, which can be developed with a psychomotor design based on physical literacy. Methods used in this service are the lecture method, mentoring, and measurement of results. Results of this service emphasize the importance of compiling LKPD that not only focuses on basic movement skills such as balance and coordination, but also encourages students' reflection on their physical experiences. Practice session allows participants to design LKPD with the guidance of a facilitator, although some still face challenges in determining measurable physical literacy indicators. Discussion and practice help teachers understand the importance of holistic measurement in psychomotor learning. Reflections at the end of the session showed that teachers gained new insights into the benefits of physical literacy integration, which is expected to improve the quality of teaching and create an inclusive learning environment that supports students' comprehensive development.